CSAVA Pull / Nazrin Ghazali, Mohammad Najmuddin Suriani and Mohamad Khairul Haziq Mohamad Fauzi - Ghazali, Nazrin; Suriani, Mohammad Najmuddin; Mohamad Fauzi, Mohamad Khairul Haziq (Faculty of Plantation and Agrotechnology, 2023)
Casava planting practice in one of the common crops planted in Malaysia. Although the casava industry is nothing comparable to another major crop but it is still important towards the cultivators in this area. To the date, there are no efficient technologies or tools that can be used to harvest the plant. The only way to do it by digging manually by using hoes. Realizing this matter, NaNaHa group has come up with innovation to effectively harvest the cassava in order to cope with certain problems that are faced before by the traditional method. The innovation will help in reducing the labor need, labor cost, management cost and on field cost.